KAJIAN NUMERIK JARAK PENGAKU BADAN DIAGONAL LINK GESER PADA STRUKTUR BAJA ECCENTRICALLY BRACED FRAME TYPE–D - Kurdi Kurdi; Bambang Budiono; Yurisman Yurisman (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
Abstract: Eccentrically braced frame type-D (EBF-D) of steel structure with shear link web stiffener is modeled in this study using MSC Nastran software. The monotonic and cyclic loading will be given under the displacement control. The shear link structure model with the vertical web stiffeners are designed with the spacing accordance to the provisions of AISC 2005. Other model is designed with shear link web stiffener diagonal with spacing between 30tw-d/5 to length of link (e) or designed ineligible to AISC 2005. The parameters of EBF-D with web stiffeners will be meansured to : configuration of the web stiffeners, the space of stiffener (a), length of the link (e), thickness of web link (tw), thickness of flange link (tf) and the thickness vertical web stiffeners (tsv) and diagonal (tsd). The results show that the performance of the portal structure of EBF-D shear link diagonal of web stiffener is better than vertical web stiffener both in terms of strength, stiffness, ductility and the absorption of energy dissipation due to earthquake loads. Optimal space between vertical web stiffeners using diagonal web stiffener is 1.6 by (30tw-d/5) with minimum thickness of diagonal web stiffener is 5.5 mm or equal which thickness web link and thickness minimum vertical web stiffeners is 8 mm.Keywords : : eccentrically braced frame type-D (EBF-D), shear link, monotonic loading, cyclic loading, diagonal web stiffener , vertical web stiffeners, strength, stiffness, ductility and energy of dissipations.Abstrak: Struktur portal baja Eccentrically Braced Frame type–D (EBF-D) dengan link geser berpengaku badan dimodelkan dalam penelitian ini menggunakan perangkat lunak MSC Nastran. Pembebanan diberikan secara monotonik dan siklik dengan kontrol perpindahan. Model struktur link geser berpengaku badan vertikal didesain dengan jarak pengaku sesuai dengan ketentuan AISC 2005. Model yang lain didesain menggunakan link geser berpengaku badan diagonal dengan jarak pengaku antara 30tw-d/5 sampai dengan panjang link (e) atau didesain tidak memenuhi syarat AISC 2005. Parameter konfigurasi pengaku badan diagonal, jarak pengaku (a), panjang link (e), tebal badan link (tw), tebal sayap link (tf) dan tebal pengaku vertikal (tsv) maupun diagonal (tsd) diteliti dalam penelitian ini. Hasil penelitian menunjukkan kinerja struktur portal EBF-D link geser berpengaku badan diagonal lebih baik dibandingkan dengan berpengaku vertikal dari segi kekuatan, kekakuan, daktilitas maupun penyerapan energi dissipasi akibat beban gempa. Jarak optimal antara pengaku badan vertikal yang menggunakan pengaku diagonal diusulkan sebesar 1,6 (30tw-d/5) dengan ketebalan minimum pengaku badan diagonal 5,5 mm atau sama dengan tebal badan dan 8 mm untuk tebal minimum pengaku vertikal.Kata kunci : Eccentrically Braced Frame type–D (EBF-D), link geser, beban monotonik, beban siklik, pengaku badan diagonal, pengaku badan vertikal, kekuatan, kekakuan, daktilitas dan energi dissipasi.